Conformations and solution structure of polyelectrolytes in poor solvent - Limbach, Hans Jörg; Holm, Christian; Kremer, Kurt (Macromolecular symposia., 2004)
Using extensive Molecular Dynamics (MD) simulations we study the behavior of polyelectrolytes in poor solvents, where we take explicitely care of the counterions. The resulting pearl‐necklace structures are subject to strong conformational fluctuations, only leading to small signatures in the form factor, which is a severe obstacle for experimental observations. In addition we study how the necklace collapses as a function of Bjerrum length. At last we demonstrate that the position of the first peak in the inter‐chain structure factor varies with the monomer density close to $ρ^{1/3}_{m}$ for all densities. This is in strong contrast to polyelectrolyte solutions in good solvent.